Analisis Faktor Penyebab Klaim Konstruksi dan Penyelesaian Sengketa pada Proyek Bangunan Gedung Pemerintah Kota Jambi - Maryan, Debi; Handayani, Elvira; Zulfiati, Ria (Jurnal Civronlit Unbari, 2026)
The construction sector plays a strategic role in Indonesia's national development, contributing 7.84% to the Gross Domestic Product in 2021. However, the complexity of construction projects often leads to conflicts that potentially trigger claims between project owners and contractors. This study aims to analyze the factors causing construction claims and dispute resolution solutions in government building projects in Jambi City. The research methodology combines primary data through questionnaire distribution to 40 medium-qualified (M1) contractor respondents and secondary data from the Jambi Province Construction Company Directory. The questionnaire instrument applies a Likert scale with four alternative answers, and data analysis was conducted using Microsoft Excel 2010. Field data collection was carried out from September 12-18, 2023, through direct visits to respondent offices. The research results identify six main factors causing conflicts with potential claims: (1) conflicts in design and specifications disadvantaging contractors (mean=4.8; ranking 1), (2) schedule changes ordered by project owners (mean=4.7; ranking 2), (3) delays caused by project owners (mean=4.5; ranking 3), and three other factors with mean values of 4.4 (ranking 4). The most dominant variables include: material standards that are no longer produced, additional work ordered by project owners, and delays in shop drawing approval. Respondent characteristics show dominance in the 31-40 age group (52.38%), bachelor's degree education (66.67%), and 6-15 years work experience (66.67%). The most effective dispute resolution solution is negotiation (mean=4.9), followed by arbitration (mean=4.6), mediation (mean=4.4), and litigation (mean=3.075). These findings provide strategic input for construction stakeholders to anticipate potential conflicts through mature planning, effective communication, and appropriate dispute resolution mechanisms.